Early intervention in psoriasis: Where do we go from here? - Felix, Paulo Antônio Oldani; Sampaio, Ana Luisa; Silva, Bruno Leonardo; Viana, Analia Luiza Porto (Frontiers in Medicine, 2022)
Patients with psoriasis often have comorbidities and are at increased risk of developing several complications compared with the general population. Knowledge on the role of immune mediators and systemic inflammation in psoriasis has led to the hypothesis that early intervention with systemic therapy has the potential to modify the course of the disease and reduce the risk of long-term adverse outcomes. In this article, we address some potential issues that need to be considered before early intervention can be implemented routinely. The first is determining what constitutes “early” intervention for psoriasis. A second point is whether the intervention should be considered for patients with early disease or for selected subsets based on risk stratification. A third important consideration is defining success for early intervention. Finally, adoption of early and effective intervention should be based on high-level evidence. Ideally, randomized trials would be the best strategy to compare early vs. late systemic treatment in patients with psoriasis, probably using the frequency of long-term outcomes as primary endpoint, with cutaneous and pharmacoeconomic outcomes assessed secondarily.